Experimental Test Analysis of Light Steel Composite Concrete Panels - Cristian Daud Wibisono; Sri Wiwoho Mudjanarko (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
The need of innovation in construction technology has driven involved parties within the industry to keep researching for new methods or materials in which could bring efficiency, yet more reliable. In this research, composite concrete panels which has become commonly used, is going to be modified by implementing lightweight steel as its concrete reinforcement. Three model of lightweight steel composite concrete panels were designed and tested for its compressing strength after 14 days. The proposed model was designed for low budget small housing and should be easily implemented. Moreover, all of the model used 1:2:3 concrete mix design without adding addictive solvent or other composite material. The tests result for model A is 5000 KN, for model B is 4600 KN and lastly for model C is 6000 KN. Based on these compressing strength test results, the designed models are able to be implemented for small housing construction.